The challenges of regional integration policy and multilevel governance in the Economic Community of the West Africa States - Kathleen Rocheteau Gomes Coutinho; Paulino Oliveira do Canto (Monções, 2018)
Regional integration is a complex process of supranational relations in order to respond to the challenges of the national, regional and international conjuncture. It is understood that in order to respond to the challenges of regionalization in this case, the Economic Community of West African States (ECOWAS) must gradually move to multilevel governance, which therefore plays a crucial role in the development of regional integration policies. Based on the neofunctionalist theory, this paper has as main objective to understand the influence of multilevel governance in the development of regional integration policy in ECOWAS. This article is based on a qualitative analysis, using data collected through documents from secondary sources. This is a comprehensive analysis of multilevel governance and the challenges of regional integration policy in ECOWAS. The results, after a systematic analysis of the available data, show that multilevel governance in ECOWAS began with the structural and regulatory reforms of the Revised Treaty of 1993 and a number of other mechanisms which allowed the sharing of the objectives of the Community with the other institutions, in addition to the Conference of Heads of State and Government and non-state actors.